Impact of Covid-19 on the mental health, quality of life and level of physical activity in university students - Ana Paula Rodrigues dos Santos; Joyce Neire Vidal Alexandre Souza; Bruno Rafael Vieira Souza Silva; Emília Chagas Costa; Marcela Claudia de Paula Oliveira Oliveira; Jael Maria de Aquino; Marcos André Moura dos Santos; Mauro Virgílio Gomes de Barros; Lygia Maria Pereira da Silva; Marco Aurelio de Valois Correia Junior (Revista Brasileira de Atividade Física e Saúde)
Young people can have negative repercussions on their mental health, quality of life and on illnesses related to physical inactivity due to social isolation and fear of the disease (Covid-19). This study aimed to analyze the impact of the Covid-19 pandemic on the quality of life, level of physical activity and mental health of university students. College students (16-24 years old) completed an online interview, considering possible changes in mental health, quality of life and physical activity level, evaluating the moment before and during the pandemic. The recruitment strategy of the participants was the snowball type. 1,167 young people (69.2%-women) attended in the study, of which 8.8% had a confirmed diagnosis of Covid-19. There was a worsening in all scores of quality of life, stress and depression during the pandemic when compared to the period prior to the pandemic (p < 0.001). The pandemic also increased inactivity among young people (49.1% vs 28%, p < 0.001). Female students, from the health area, who had their own home and who did not have confirmed diagnosis of Covid-19 showed increased stress in the pandemic period. The Covid-19 pandemic worsened the indicators of mental health, quality of life and level of physical activity among university students. It is noteworthy that despite not being a risk group for the aggravation of the disease and consequent higher mortality, restrictions related to the pandemic limited or prevented the movement of people and this isolation can represent important changes in health in the medium and long term in this population.